Disembodied behavior and communication effectiveness in learning activity during the Covid-19 pandemic era - Suwatno Suwatno; A. Adman; Hady Siti Hadijah; Fahmi Jahidah Islamy; Aeng Muhidin (Informasi, 2022)
Currently, Corona is a hot topic of discussion. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2), better known as the coronavirus, is a new type of coronavirus that causes infectious diseases in humans. The online learning system (on the network) is the answer for universities to continue to carry out academic activities. Online learning is a learning system without face-to-face directly between lecturers and students but is done virtually. Lecturers must ensure that teaching and learning activities continue while students are at home. The solution is that lecturers must be able to design learning activities as innovations by utilizing online media to continue running effectively. Communication between students and lecturers through video conferencing raises several problems: the low creativity of students, the difficulty of achieving communication effectiveness, and generating demotivation and disembodied behavior. The purpose of this study was to determine the level of (1) effectiveness of virtual lecturer communication based on student perspectives, (2) student demotivation, (3) student disembodied behavior, and (4) student creativity. This research uses a descriptive method. The sampling method used is incidental sampling, where the subjects studied are lecturers and students willing to participate in filling out research questionnaires. The number of lecturers in this study was 91 people from 25 universities in the city of Bandung, with a total of 100 courses, so a sample size of 200 sampling units was obtained, where the sampling unit was lecturer-subjects. The results showed that the student creativity variable was in the high category, the demotivating variable was in the low category, the disembodied behavior variable was in the moderate category, and the lecturer's communication effectiveness variable was in the very high category